DIFFERENCES OF ANTROPOMETRICAL CHARACTERISTICS IN RELATION TO SEX OF PUPILS - Goran Gojković; Branislav Radulović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
As per sample of 212 examinees at the age of 11 (±6 months) at the fifth grade in Montenegrin elementary schools, it was used the system of 12 variables for the estimation of anthropometrical characteristis. The purpose of the examination was to establish differentiations between different students sex in the initial and final measuring. As for results given by using discriminant analysis and univariant analysis of variance on the anthropometrical student's status, it can be concluded that there's a statistical significant level in discrimination of subsamples of different sex.